Prevalence of New-Onset Otological Symptoms in Patients with Temporomandibular Disorders - Mirko Aldè; Henri Albert Didier; Aldo Bruno Giannì; Fabiola Sessa; Giulia Borromeo; Alexandre Henri Didier; Stefania Barozzi; Diego Zanetti; Federica Di Berardino (MDPI AG, 2022)
The aim of this retrospective study was to evaluate the prevalence of new-onset otological symptoms and the possible associations between tinnitus and oral parafunctional habits among patients with temporomandibular disorders (TMD) who attended a Craniofacial Pain Outpatient and a Dentistry Clinic. The medical reports and charts of patients who experienced TMD between 1 February 2016 and 31 December 2017 were reviewed, in order to evaluate the prevalence of new-onset aural fullness, vertigo and tinnitus. Tinnitus was also analyzed in more detail to evaluate possible associations with parafunctional habits. A total of 400 patients (301 females, 99 males) met the inclusion criteria, with a median age of 39.6 ± 15.6 years. Overall, new-onset otological symptoms were reported by 304 (76%) subjects with TMD. Among otological symptoms, aural fullness was the most common (n = 133, 33.3%), followed by tinnitus (n = 92, 23%) and vertigo (n = 79, 19.8%). No significant correlations were found between tinnitus and bruxism (p = 0.28), clenching (p = 0.11), nail-biting (p = 0.96), sleeping prone (p = 0.27), chewing gum (p = 0.99) and talking for a long time (p = 0.42). The present study suggests that all patients with TMD should be investigated for new-onset otological symptoms, regardless of oral parafunctional habits. Early diagnosis would allow to plan personalized and appropriate therapeutic and rehabilitative pathways, minimizing the negative impact due to TMD.